Título Padrão - Pavarina, Etefania Cristina (Informação em Pauta, 2022)
This research discusses the indexing of a comic strip based on the theoretical and methodological constructs of Greimasian semiotics, with a focus on the generative path of sense. It aims to identify elements of the generative path of sense that can help in the process of indexing the comic strip. Methodologically, it is an exploratory study, of applied character and qualitative approach. It is also characterized as a bibliographic research, performed in the Reference Database of Articles from Periodicals in Information Science (BRAPCI), Brazilian Digital Library of Theses and Dissertations (BDTD), Repository of presentations and lectures from the National Meetings on Research and Graduate Studies in Information Science (BENANCIB), Library and Information Science Abstracts (LISA) and Library, Information Science and Technology Abstracts (LISTA). The results are based on the use of the content analysis method. As results it is presented guidelines for the indexing of comic strips based on the generative path of sense for the extraction of the terms of indexing and preparation of the abstract. It is concluded that the meaning-generative path assists in comic strip indexing, directing the reading of the document and providing strategies that reduce the subjectivity of the indexing process and ambiguity in understanding the meanings intrinsic to the information resource.